The Application of Information Technology Architectural Design Using TOGAF Architecture Framework in Restaurant Service Systems - Sri Wahyuningsih, Suluh; Ziaul Haq, Muhammad; Hamid, Helson; Hady, Sultan; Hendrawan, Nalis (Jurnal Informasi dan Teknologi, 2023)
This research aims to see how TOGAF ADM is applied to modeling information technology architecture in restaurants. In this research, the author used the TOGAF Architecture Development Method (ADM). In TOGAF ADM, there is a definition of architecture and its understanding, which is in the preliminary phase (the preparatory phase). In this modeling, it starts from zero, so a detailed architectural process is needed. This is needed to simplify the subsequent architectural development process. Detailed architectural processes can be obtained using the framework. In TOGAF ADM, there are stages that have been arranged in such a way that the details of the architecture can be seen in them. The modeling that the author will compile also requires support for architectural evolution. This is needed because, initially, the restaurant did not have technological architecture. In Phase F Migration Planning, the framework provides support for technology architecture evolution. Based on the research steps, there are 8 structured stages plus a preliminary stage. However, in this research, the author will only discuss up to stage F, namely migration planning. From the research conducted by the author, a model of information technology architecture for restaurants was obtained, which was implemented using TOGAF ADM. The information technology architecture model includes service processes, payment processes, and monitoring processes.